2015
DOI: 10.1186/s13024-015-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Human neural stem cells alleviate Alzheimer-like pathology in a mouse model

Abstract: BackgroundAlzheimer’s disease (AD) is an inexorable neurodegenerative disease that commonly occurs in the elderly. The cognitive impairment caused by AD is associated with abnormal accumulation of amyloid-β (Aβ) and hyperphosphorylated tau, which are accompanied by inflammation. Neural stem cells (NSCs) are self-renewing, multipotential cells that differentiate into distinct neural cells. When transplanted into a diseased brain, NSCs repair and replace injured tissues after migration toward and engraftment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 74 publications
(86 reference statements)
6
106
0
Order By: Relevance
“…Recently, emerging studies reported transplantation of hNSCs in mice with various disease models (Lee I.-S. et al, 2015; Zuo et al, 2015; Haus et al, 2016). While some studies reported the differentiation failure of engrafted hNSCs in mice (Lee S.-R. et al, 2015), more studies showed the predominant differentiation of hNSCs into astrocytes (Gao et al, 2006; Lee I.-S. et al, 2015). The different differentiation patterns could be associated with the source of human cells, cell preparation, as well as difference in animal models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, emerging studies reported transplantation of hNSCs in mice with various disease models (Lee I.-S. et al, 2015; Zuo et al, 2015; Haus et al, 2016). While some studies reported the differentiation failure of engrafted hNSCs in mice (Lee S.-R. et al, 2015), more studies showed the predominant differentiation of hNSCs into astrocytes (Gao et al, 2006; Lee I.-S. et al, 2015). The different differentiation patterns could be associated with the source of human cells, cell preparation, as well as difference in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Cell rejection is an ongoing issue challenging the NSC transplantation therapy especially for using xenogeneic transplants (Lee I.-S. et al, 2015). Due to difference in cell sources and transplantation sites, the survival and differentiation rates of implanted xenogeneic NSCs are differently reported across studies (Ager et al, 2015; Haus et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular therapies represent a potential disease‐modifying treatment for Alzheimer's disease (AD), with multifaceted therapeutic benefits including tissue replacement, secretion of neuroprotective trophic factors, and/or modulation of inflammation 1, 2, 3, 4, 5, 6. As such, transplantation of stem cells from various sources into the hippocampus improves cognitive impairment in murine AD models 1, 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, transplanted cells modulate diverse AD pathologies and rescue impaired memory via multiple mechanisms in an AD model [76,77] .…”
Section: (3) Enhancing Endogenous Synaptogenesismentioning
confidence: 99%